InfraRed Astronomy Satellite Swarm Interferometry (IRASSI): Overview and study results. Issue 2 (15th January 2020) - Linz, Hendrik; Bhatia, Divya; Buinhas, Luisa; Lezius, Matthias; Ferrer, Eloi; Förstner, Roger; Frankl, Kathrin; Philips-Blum, Mathias; Steen, Meiko; Bestmann, Ulf; Hänsel, Wolfgang; Holzwarth, Ronald; et al.
Abstract: The far-infrared (FIR) regime is one of the few wavelength ranges where no astronomical data with sub-arcsecond spatial resolution exist yet. Neither of the medium-term satellite projects like SPICA, Millimetron or OST will resolve this malady. For many research areas, however, information at high spatial and spectral resolution in the FIR, taken from atomic fine-structure lines, from highly excited carbon monoxide (CO) and especially from water lines would open the door for transformative science. These demands call for interferometric concepts. We present here first results of our feasibility study IRASSI (Infrared Astronomy Satellite Swarm Interferometry) for an FIR space interferometer. Extending on the principal concept of the previous study ESPRIT, it features heterodyne interferometry within a swarm of five satellite elements. The satellites can drift in and out within a range of several hundred meters, thereby achieving spatial resolutions of <0.1 arcsec over the whole wavelength range of 1–6 THz. Precise knowledge on the baselines will be ensured by metrology methods employing laser-based optical frequency combs, for which preliminary ground-based tests have been designed by members of our study team. We first give a motivation on how the science requirements translate into operational and design parameters for IRASSI. Our consortium has put much emphasis on the navigational aspects of such a free-flying swarm of satellites operating in relatively close vicinity. We hence present work on the formation geometry, the relative dynamics of the swarm, and aspects of our investigation towards attitude estimation. Furthermore, we discuss issues regarding the real-time capability of the autonomous relative positioning system, which is an important aspect for IRASSI where, due to the large raw data rates expected, the interferometric correlation has to be done onboard, in quasi-real-time. We also address questions regarding the spacecraft architecture and how a first thermomechanical model is used to study the effect of thermal perturbations on the spacecraft. This will have implications for the necessary internal calibration of the local tie between the laser metrology and the phase centres of the science signals and will ultimately affect the accuracy of the baseline estimations.